2019
DOI: 10.1029/2019gc008309
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing Deep Geothermal Upflow in Zones of Complex Tectono‐Volcanic Degassing: New Insights from Aluto Volcano, Main Ethiopian Rift

Abstract: Active rifts release large amounts of gases from deep sources to the atmosphere by advection and diffusion processes along permeable fracture zones. The objective of this study is to develop geothermal exploration concepts for areas with little or no hydrothermal surface expressions suitable for fluid sampling and analyses (e.g., hot springs, geysers, and fumaroles). In such areas, soil gas surveys can complement established geophysical and geochemical exploration. We report CO2, 222Rn (radon), and 220Rn (thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Specific areas with obvious gas emissions are often sampled with a higher density of measurements for a more accurate detection of variations in soil gas emissions and delineation, whereas areas with less obvious gas emissions are often not taken into account (Werner et al, 2000;Chatterjee et al, 2019) despite the chance of missing permeable structures (hidden faults). Multiple studies showed the advantage of regular spaced surveys (e.g., Werner et al, 2000;Jolie et al, 2019). Systematic grid sampling is an effective and unbiased concept to collect spatially correlated data over a large area (geothermal reservoir scale) whilst avoiding interpolation artefacts (Isaaks and Srivastava, 1989) and allowing a detailed estimation of the total CO2 output (combined advective and diffuse degassing) (Lee et al, 2016).…”
Section: Sampling Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific areas with obvious gas emissions are often sampled with a higher density of measurements for a more accurate detection of variations in soil gas emissions and delineation, whereas areas with less obvious gas emissions are often not taken into account (Werner et al, 2000;Chatterjee et al, 2019) despite the chance of missing permeable structures (hidden faults). Multiple studies showed the advantage of regular spaced surveys (e.g., Werner et al, 2000;Jolie et al, 2019). Systematic grid sampling is an effective and unbiased concept to collect spatially correlated data over a large area (geothermal reservoir scale) whilst avoiding interpolation artefacts (Isaaks and Srivastava, 1989) and allowing a detailed estimation of the total CO2 output (combined advective and diffuse degassing) (Lee et al, 2016).…”
Section: Sampling Approachmentioning
confidence: 99%
“…Such low efflux values typically originate from biogenic sources (i.e. plant and microbial respiration and organic decomposition; see also Werner et al, 2000;Cardellini, 2003;Peiffer et al, 2014;Hutchison et al, 2015;Jolie et al, 2019). In fact, maximum CO2 efflux values reported for biogenic sources generally range from below detection limit of the device up to a few tens of grams per square meter and day in highly vegetated areas, but never exceed 100 g m -2 d -1 (Chiodini et al, 2007;Raich and Tufekcioglu, 2000;Widén and Majdi, 2011).…”
Section: Population Amentioning
confidence: 99%
See 1 more Smart Citation
“…At the most fundamental level, faults and fracture systems serve as channels for geothermal fluids [64][65][66][67] from hot deeper levels of the crust to within a few kilometres of the surface, where wells can tap the fluids for power production. Conversely, such structures also facilitate the circulation of meteoric fluids from near the surface to deeper crustal levels (termed recharge), which is essential for sustaining broad convective geothermal systems 39 .…”
Section: Outflow Zonesmentioning
confidence: 99%
“…Although the deep (km-scale) architecture of these volcanic-geothermal systems is best imaged by magnetotellurics, high-spatial resolution (~10-50 m) gas surveys are particularly powerful at identifying permeability and pinpointing drilling locations (Jolie et al, 2019). Though many of East Africa's geothermal resources fit this model and are intimately associated with silicic caldera complexes there are various sites which show geothermal manifestations and high fluxes of magmatic volatiles, but no surface volcanism.…”
Section: Introductionmentioning
confidence: 99%